Pelatihan Massage di Komplek Perumahan Adinegoro Indah Kelurahan Batang Kabung, Kecamatan Koto Tangah, Kota Padang - Yuni Astuti; Ali Mardius (LPPM UNINUS, 2017)
Devotion of science and technology for the community is implemented to transfer knowledge and skills how to do Massage In woman di Komplek Perumahan Adinegoro Indah RT 003/RW 015 Kelurahan Batang Kabung Kecamatan Koto Tangah Padang. The importance of massage done because the daily activities are very dense make the body tired and stiff need of relaxation. The occurrence of fatigue (fatigue) is a physiological phenomenon, a process of the occurrence of a state of decreased tolerance of physical work, the cause is very specific depending on work characteristics. The cause of fatigue is also due to the accumulation of lactic acid is a by-product of the metabolism of energy formation. In our bodies, there is a chemical process that converts chemical energy into food into mechanical energy that allows our muscles to contract. To reduce fatigue caused by lactic acid is one way that can be done is with massage. The effects of massage on blood circulation, lymph, skin, muscle and nerve according to, are described as follows: a) Effect of Sport massage on blood circulation and lymph, b) Effect of Sport massage on skin, c) Sport massage effect on muscle tissue and d) Effect Sport massage against innervation.